Interactive Effects of Soil pH and Organic Matter on Phosphorus Solubility and Maize Yield in Calcareous-Acid Mixed Soils: Interactive Effects of Soil pH and Organic Matter - Parvez, Md Masud; Khan, Md Harunor Rashid (South Asian Journal of Agriculture, 2025)
Low Phosphorus (P) availability is one of the greatest limitations in acid and calcareous soils mainly because it is fixed and therefore its movement and uptake by plants are hindered. This study evaluated the joint actions of soil mixing ratios and organic amendments on soil properties, P dynamics, maize (Zea mays L.) productivity, and grain P concentration. Two mixing ratio of calcareous and acid soil (1:1, 1:2, and 1:3) and seven organic amendment treatments, namely, vermicompost, mixed compost and Tricho-compost applied at two rates and a control gave a factorial experiment. The soil organic matter (OM), pH, available P at 40 days of treatment application and after harvest, maize yield, and grain P were tested. The 1:3 mixing ratio (one-part calcareous soil with three parts acid soil) consistently produced the highest OM, available P at 40 days and grain P content, which demonstrated better P mobility under less calcareous conditions. These organic amendments that significantly increased available P and grain P as compared to the control were Tricho-compost at 8 t/ha, vermicompost at 8 t/ha and mixed compost at 4 t/ha. OM content and pH buffering were also enhanced through organic amendments whose effects improved nutrient availability. Correlation analysis revealed that there were strong positive correlations of OM and available P (40 days) (r = 0.37, p < 0.01), and pH (after harvest) and available P (after harvest) (r = 0.48, p < 0.01). Grain P had a weak positive correlation with available P at 40 days. There were no significant correlations between maize yield and soil chemical properties and it can be assumed that other variables (e.g. moisture, other macro or micronutrient interactions, etc.) might have influenced the ultimate yield. Such results demonstrate the relevance to consider integrating soil mixing strategies with organic sources of nutrients in reducing P fixation, increasing P-use efficiency, and enhancing nutritional quality of crops in P-deficient agroecosystems. More long-term research is encouraged in order to ensure sustainability and optimize amendment rates. South Asian J. Agric. Vol. 11, No. 2, Dec., 2025: 100-116